PENGARUH INISIASI MENYUSU DINI TERHADAP PENINGKATAN PENGELUARAN ASI PADA 24 JAM PERTAMA POST PARTUM DI RUANG MAWAR 1 RSUD DR. MOEWARDI TAHUN 2011 - Irfani, Dhina Nur; Sutanta, Sutanta (Jurnal Kesehatan Samodra Ilmu (JKSI), 2013)
ABSTRACK Background: Early Initiation of Breastfeeding cause skin contact with the mother and baby skin optimally. Research shows when the first 24 hour after the baby is born baby lying on mother’s chest will follow the same pattern with hand gestures to find and stimulate the mpther’s breast so that more oxytocin is issued. Method: This study aims to investigate the influence of Early Initiation of breastfeeding on discharge ASI 24 Post Partum. This study was designed to approach pretest – posttest with control group, the design of this study will take measurements or observation before and after treatment are given. Statistic test used for this study used SPSS version 16 with Independent T –test. Result: Correlation result of this study using statistical analysis through test independent sample alpha test with siginifocant level (0,05). Obtain significance figures for 0.002. from these results show there are significant differences in outcomes between the 2 varibles so that Ha is accepted. Conclussion: The study concluded “ There Influence Early Of Breastfeeding to Increase Spending On 24-hour Mother’s milk First Post Partum at 1 Hospital Dr.Moewardi the Year 2011”